Caracterización Geológica – Geotécnica a Escala 1:5000 de la Vía Villonaco – Taquil, Kilómetro 9,5 – 12,00 Cantón y Provincia de Loja - Espinosa Albia, Renato Alejandro (2024)
This research paper "Geological - Geotechnical Characterization at Scale 1:5000 of the Villonaco - Taquil Road, from section absc. 9+500 to 12+000 located between Cera neighborhood and Taquil parish, Loja canton, Loja province" aims to produce a geological-geotechnical characterization of the aforementioned section of road, primarily focused on a geological-structural survey and characterization of the area, the determination and characterization of the physical-mechanical properties of the existing geomaterials along the road, and the ascertainment of the safety factor of critical areas found, such as "mass movements," along the road. The study area spans 2.50 km and covers an area of 108.46 hectares. The first stage of the investigation was a detailed topographic survey carried out by photogrammetry with the help of a Phanton 4 Drone and the software programs Pix4D and ArcMap, resulting in a topographic map at a scale of 1:5000 showing an irregular relief, with heights ranging from 2120 m.a.s.l. (lowest elevation) to 2330 m.a.s.l. (highest elevation). Subsequently, based on the topographic map, a local geological survey was carried out, where a total of 20 outcrops were identified during which time samples were collected for macroscopic description. During this stage, it was determined that the area consists mainly of basaltic lavas, volcano-sedimentary sequences, conglomerate levels, hypoabyssal rhyolitic bodies, gabbro and diorite intrusions of the Gonzabal Unit and schists of the Cera Unit, in addition to colluvial deposits with a predominance of angular blocks of volcanic rocks. For the identification and characterization of the physical-mechanical properties of the geomaterials in the study area, data was obtained from the following; 2 subgrade test pits which were used to determine the bearing capacity and type of soil on which the road is located, through CBR and classification according to SUCS and ASSTHO; 2 direct shear tests on slopes showing indicators of future instability under possible lateral loads or forces; 4 seismic refraction lines, 2 test pits, 2 triaxial compression tests and 3 SPT's tests in strategic points of the 2 landslides studied; and 3 tests of resistance to simple compression, 3 tilt tests, 3 low impact sclerometry tests and determination of physical properties according to ASTM - D 854-58, ASTM C - 128-07, ASTM D 2216 - 98 and ASTM C 127-01 standards, in cores and rock samples of the 4 rock massifs studied. The geomechanical classification of each massif was carried out using the RMR and GSI. Thus, for the stability analysis of the rock massifs, we proceeded first with the stereographic analysis of the families of discontinuities using Dips software to effectively evaluate the distribution of discontinuities and their influence on stability; subsequently, the resistance analysis of the rock massifs was performed using the generalized Hoek & Brown approach adjusted to the Mohr - Coulomb criterion in Roclab software. Finally, to determine the safety factor, a global stability analysis was carried out in its current state with seismic and static loads for the landslides and rock masses, using limit equilibrium methods in GeoStudio R2 and Slide 7.0 software’s. Keywords: geomaterials, factor of safety, photogrammetry, subgrade, bearing capacity, CBR, SUCS, ASSTHO, seismic refraction, SPT testing, geomechanical classification, stereographic analysis, Hoek & Brown and Mohr Coulomb criteria